Incidence and Outcome of Pneumomediastinum in Non-ICU Hospitalized COVID-19 Patients*. Issue 1 (5th October 2022) - Muley, Moises; Finamore, Panaiotis; Pedone, Claudio; Margiotta, Domenico Paolo Emanuele; Gilardi, Emanuele; Sambuco, Federica; De Vincentis, Antonio; Vespasiani-Gentilucci, Umberto; Travaglino, Francesco; Antonelli-Incalzi, Raffaele
Abstract : OBJECTIVES: Pneumomediastinum (PNM) is a rare complication of mechanical ventilation, but its reported occurrence in patients with acute respiratory distress syndrome secondary to COVID-19 is significant. The objective is to determine the incidence, risk factors, and outcome of PNM in non-ICU hospitalized patients with severe-to-critical COVID-19 pneumonia. DESIGN: Retrospective observational study. SETTING: Population-based, single-setting, tertiary-care level COVID treatment center. PATIENTS: Individuals hospitalized with a diagnosis of COVID-19 pneumonia and severe to critical illness were included. Those hospitalized without respiratory failure, observed for less than 24 hours, or admitted from an ICU were excluded. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: All patients underwent a complete clinical assessment and chest CT scan, and were followed up from hospitalization to discharge or death. The outcome was the number of cases of PNM, defined as the presence of free air in the mediastinal tissues diagnosed by chest CT scan, in non-ICU hospitalized patients and the subsequent risk of intubation and mortality. PNM occurred in 48 out of 331 participants. The incidence was 14.5% (95% CI, 10.9–18.8%). A CT-Scan Severity score greater than 15 was positively associated with PNM (odds ratio [OR], 4.09; p = 0.002) and was observed in 35.2% of the participants (95% CI, 26.2–44.9%). Noninvasive ventilation was also positively associated with PNM (OR, 4.46; p = 0.005), but there was no positive association with airway pressures. Fifty patients (15%) were intubated, and 88 (27%) died. Both the risk for intubation and mortality were higher in patients with PNM, with a hazard ratio of 3.72 ( p < 0.001) and 3.27 ( p < 0.001), respectively. CONCLUSIONS: Non-ICU hospitalized patients with COVID-19 have a high incidence of PNM, increasing the risk for intubation and mortality three- to four-fold, particularly in those with extensive lung damage. These findings help define the risk and outcome of PNM in severe-to-critical COVID-19 pneumonia in a non-ICU setting.